Affording Homes in Yogyakarta: An Empirical Analysis of Local Housing Market Affordability - Bagaskara; Yudistira Permana; Maygsi Suwandi (Jurnal Ekonomi Kuantitatif Terapan, 2026)
Issues surrounding the difficulty of buying a house for local people in the Special Province of Yogyakarta are undeniable. This raises the question: can local residents afford a decent house? This study aims to develop a framework to describe housing affordability using surveys and econometric methods. A hedonic price model was created based on data from 174 houses in urban areas in Yogyakarta. This model estimates house prices considered appropriate, derived from a survey of 283 local residents who do not own a house. The results indicate that local residents cannot afford to buy a house. The regression model estimates house prices higher than the mean or median values of respondents' perceptions of affordability. Surveyed respondents deemed houses with minimum specifications as follows: a lot size of 53.6 m², building size of 89.4 m², front road width of 4.4 m, and a distance of 2.7 km to shopping facilities. The estimated price for such housing ranges between IDR 300,000,000 and IDR 400,000,000. These findings highlight a gap between market prices and local affordability. The government can use these specifications as input to design policies that provide affordable housing for local residents in Yogyakarta